1 and 2 Corinthians - Bruce, Frederick Fyvie, 1910-1990 (Grand Rapids, MI Eerdmans, 1971)
Includes bibliographical references and indexes.
Brethren writer.
Keywords: Bible. N.T. Corinthians -- commentaries